Increasing physical activity levels among girls in Russia: a cross-over trial - Updyke, Natalie J. (Kansas State University, 2015)
Background: Children who obtain insufficient physical activity (PA) have increased risk for chronic diseases. From childhood to adolescence, there is typically a decline in overall PA, with a more rapid decline in girls, at a younger age. The objective of this study was to determine the impact of two types of organized PA instructional conditions (structured no-choice, structured choice) on girls’ PA levels, as compared to free-play at a summer camp in Russia. We hypothesized that free-play would elicit the highest levels of PA. Methods: This study used a within-subjects cross-over trial design. Thirty-two girls (aged 10.7± 0.6yr; BMI percentile 47± 31%) at a Russian summer camp, attended daily 35-minute PA sessions for three weeks. Using the evidence-based Coordinated Approach to Child Health physical activity box, three PA instructional conditions (structured choice, structured no-choice, free-play) were implemented each day. Actical PA monitors collected step count and PA intensity data. Mixed model ANOVAs were used to assess differences in step counts and percentage of time in Moderate to Vigorous Physical Activity (MVPA) by instructional condition. Results: Twenty-five of the 32 participants attended all sessions, and 31 attended at least two of three sessions for each condition. Both structured conditions, no-choice steps/min (mean= 42.7 steps/min; 95%CI= 39.6–45.7; p= 0.0003) and choice condition steps/min (mean= 41.0 steps/min; 95%CI= 37.9–44.1; p= 0.004) were significantly higher than free-play steps/min (mean= 33.4 steps/min; 95%CI= 30.2–36.5). Percent time in MVPA was higher in the no-choice condition (mean= 30.9%; 95%CI= 28.1–33.8; p<0.0001) and choice condition (mean= 30.8%; 95%CI= 27.9–33.7; p< 0.0001) when compared to free-play (mean= 21.2 steps/min; 95%CI=18.2–24.1). There was no difference in steps/min or percentage time in MVPA between both structured conditions. Conclusion: Both types of instruction were superior to free-play with regard to PA level. Although contrary to our hypothesis, our results fit with previous literature that suggests evidence-based instructional interventions can promote higher PA levels in physical education sessions. Our results suggest that well-planned, stimulating PA sessions can increase short-term PA levels in girls compared to free-play opportunities in a Russian summer camp setting.
Keywords: Physical activity intervention; Russia; Girls; Camp setting; Health Sciences, Education (0350)